METHODOLOGY OF USING SPEED-STRENGTH EXERCISES TO IMPROVE WORK CAPACITY DURING THE PREPARATORY PERIOD OF YOUNG FOOTBALL PLAYERS - Eshimov Temur Alijonovich (Bright Mind Publishing, 2026)
This article examines the methodological aspects of using speed-strength exercises to improve the physical work capacity of young football players during the preparatory period. During the research process, training sessions were conducted with football players aged 13–16, and the impact of speed-strength exercises on general and special work capacity was analyzed. The results of the study showed that properly planned speed-strength exercises adapted to age characteristics during the preparatory period significantly improve players’ explosive strength, speed, and overall work capacity during matches.
Keywords: Young football players, speed-strength exercises, preparatory period, work capacity, physical training.